Crisis Communication in a Cultural Context: A Study of Chinese Youth Participation in Natural Disaster Information Sharing - Zhang, Linghan; Fernandez, Kevin (Journal of Posthumanism, 2025)
This study investigates how Chinese youth aged 16 to 25 engage in the dissemination of natural disaster information via Douyin (the Chinese counterpart of TikTok), emphasizing the intersection of digital nativity, collectivist cultural frameworks, and a sense of civic responsibility. Employing a mixed-methods approach—integrating a systematic literature review with targeted case studies—the research analyzes youth communication patterns during major natural disasters in China from 2020 to 2024.Findings reveal that digital behavior among Chinese youth is profoundly shaped by enduring cultural logics, particularly collectivism and face-saving norms, which diverge markedly from prevailing Western communicative paradigms. Through Douyin’s platform affordances, young users assume roles as both real-time documentarians and unofficial first responders, transmitting critical information while simultaneously navigating the constraints of an intricate state-controlled media environment.This case extends crisis communication theory by proposing culturally responsive frameworks better suited to collectivist, non-Western contexts. The insights generated have practical relevance for the design of crisis communication strategies that are attuned to the cultural, political, and technological particularities of different global settings.